Organisational Socialisation Facilitates Overseas Assignment - Lee , Pei-Chen (Chiu-Yi/Joy); Cheng , Cheng-Tai (Roger) (Journal of Law and Governance, 2008)
Cross-cultural adjustment is the biggest challenge that derails expatriate success. In responding to the importance of Taiwanese expatriates’ adjustment in Mainland China, this study tests, as a critical factor, Socialisation affecting the adjustment of Taiwanese expatriates in Mainland China. As a result, this study critically reviews previous studies on expatriate success, shedding light on key factors in the area of expatriate adjustment and providing multiple guidelines for human resource supervisors and senior executives hoping to ensure expatriate success. The definitions of success and methodological approaches are discussed, and suggestions for improving empirical research in this area are presented. Academic researchers and international enterprises can perhaps clarify whether all international expatriates are affected by the factor as organisational socialisation, and also whether the proposed model can be utilised in studying expatriates in different professional areas from those of this study. Finally, the results and their implications for research and the business world are discussed. This may assist not only Taiwanese MNCs but also global enterprises to perform their international business more efficiently in Mainland China.